The quantum-confined Stark effect in layered hybrid perovskites mediated by orientational polarizability of confined dipoles - G. Walters (Nature Portfolio, 2018)
The quantum-confined Stark effect is conventionally observed in inorganic semiconductor multilayer quantum well structures that are expensive to make. Here Walters et al. report large Stark effects in easily made layered hybrid perovskites and exploit the orientational polarizability of dipolar cations.